YAP/TAZ mechano-transduction as the underlying mechanism of neuronal differentiation induced by reduced graphene oxide. (19th November 2018) - Catanesi, M; Panella, G; Benedetti, E; Fioravanti, G; Perrozzi, F; Ottaviano, L; Leandro, L Di; Ardini, M; Giansanti, F; d'Angelo, M; Castelli, V; Angelucci, F; et al.
Aim: The aim of this work is the dissection of the molecular pathways underlying the differentiation effect of reduced graphene oxide (GO) materials in the absence of differentiation agents.Materials & methods: Reduced GO is obtained either by drop casting method and heat-treated or biological reduction by the interaction between GO and wtPrxI. Cells were grown on both materials and the differentiation process studied by immunological and morphological detection.Results & conclusion: The results obtained indicate that both reduction methods of GO can determine the modulation of pathway involved in mechano-transduction and differentiation, by affecting YAP/TAZ localization outside the nuclei and increasing neuronal differentiation markers. This suggests that the mechano-transduction pathways are responsible for the differentiation process.